Quality of Life, Anxiety and Depression among Clients with Ostomy Attending Selected Stoma Clinics - Shrestha, Sangita; Siwakoti, Susmita; Shakya, Urmila; Shakya, Rajina; Khadka, Sangita (Journal of Nepal Health Research Council, 2022)
Background: Ostomy is a part of treatment among patients which has detrimental effects in patient’s life. The main aim is to identify the quality of life, anxiety and Depression in clients with an ostomy.Methods: Descriptive exploratory study design was used. Total of 116 clients with ostomy, aged 18 years and above were selected from stoma clinics. The modified version of City of Hope and Beckman Research Institute, Quality of Life Questionnaire for Patient with Ostomy and Hospital Anxiety and Depression Scale was adopted for data collection using an interview technique.Results: The overall mean ± S.D quality of life score was 5.89 ± 1.34. Majority (59.5%) of respondents possessed low Quality of life. Among the quality of life domains, the least and most affected domains were physical (5.96±1.52) and social (4.71±1.44) respectively. Duration of having an ostomy (p<0.001), problem in clothing (p<0.002) and change in clothing style (p= 0.002) were significantly associated with the level of quality of life. Almost two-thirds of the respondents were in the borderline and abnormal level of anxiety and depression. The level of anxiety has significant association with suicidal consideration/attempt (p=.04).Conclusion: Presence of ostomy affects patient’s quality of life by increasing financial burden, adjustment difficulties, sexual and psychological problems (anxiety, depression, suicidal consideration). Sexual and psychological counselling, ostomy support groups and free health services to ostomates may improve their quality of life. Keywords: Anxiety; depression; ostomy; quality of life